Masculization of Rainbow Fish Boesmani (Melanotenia boesmani) Through Immersion Larvae Use Extract Propolis Honeybees with Long Different Times - Aditya satriani; Riza hakim; Hariyadi Hariyadi (IJOTA (Indonesian Journal of Tropical Aquatic), 2024)
Fish rainbow boesemani ( melanotaenia boesmani ) is ornamental fish freshwater economically valuable important that is fish endemic of the papua island . Fish rainbow is one of the preferred by people, because it has morphology the body and pattern of coloration that is distinctive and unique having an elongated flattened body and color in body parts toward the head blue bright and toward the tail bright orange. Fish rainbow boesmani male more interested in people, because it has a variation of color interesting. Maskulinisasi is one of the methods by to produce the production of a male fish . One of natural materials that can be used in the methods of maskulinisasi for producing a male fish that is using propolis honeybees This research was conducted in Laboratory of Reproduction division of reproduction fish , the faculty of fisheries and of marine science, Brawijaya University Malang on december 2017 till January on a deal valid 2018 .The methodology that was used the experimental methods are using ral with 4 treatment ( 10jam , 12jam , 14jam , 16jam with a dose 1ppm ) and control. Data obtained the fire victims with anova were analysed and in the long term undergone a BNT. Paramater the main upon the of this study is the percentage of the male organs and the survival rate at the current level, from the supporting parameter growth rate at the current level and water quality. This research outcomes for fear of a massive the percentage of male rainbow boesemani on larvae of fish .The percentage of male on a 45,45 % treatment , b 62,35 % , c 47,78 % , d 39,49 % , and in control 11.82 % treatment .The percentage on the highest male treatment b 62,35 %. Survival treatment a 71,11 % kept its key rate at , b 58,89 % , c 48,89 % , d 42,22 % and control 90 %. As to economic growth rate a 0,0211g treatment , b 0,0209g , c 0,0210g , d 0,0210g , and control 0,0198g .The quality of water covering of temperature on the morning ranged from 22,6 to make during the day ranged from 24,1-27.7 .While the value of do to the morning ranged from 5,38 - 8,43 ppm and which excludes swings in administered during the day ranged from 5,12-7,67 ppm, pH in the morning ranges 6.5-7.8 and during the day ranged from 6.1 virtually vanished 7.3. Conclusion to research maskulinisasi fish rainbow boesemani use extract propolis honeybees to the time soaking distinct larval produce influence very real to the productions a male fish when do soaking optimally .